2020
DOI: 10.3389/fonc.2020.00915
|View full text |Cite
|
Sign up to set email alerts
|

ALDH1A3 Accelerates Pancreatic Cancer Metastasis by Promoting Glucose Metabolism

Abstract: Background: The aldehyde dehydrogenase 1 family member A3 (ALDH1A3) is a key enzyme associated with a variety of metabolic processes, including glucose metabolism. We recently uncovered that glucose metabolism played an essential role in promoting metastasis of pancreatic ductal adenocarcinoma (PDAC). As ALDH1A3 labels an aggressive subtype of PDAC, we hypothesized that ALDH1A3 functionally promoted PDAC metastasis via its metabolic effect on glucose metabolism.Methods: Expression of ALDH1A3 was detected in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…Feng et al illustrated that aerobic glycolysis could promote the growth and metastasis of hepatocellular carcinoma [ 38 ]. In pancreatic cancer, Nie et al found that ALDH1A3 promoted the metastasis of tumor cells by enhancing the glycolysis in them [ 39 ]. In our study, we divided the patients into high- and low-risk groups according to an established risk signature.…”
Section: Discussionmentioning
confidence: 99%
“…Feng et al illustrated that aerobic glycolysis could promote the growth and metastasis of hepatocellular carcinoma [ 38 ]. In pancreatic cancer, Nie et al found that ALDH1A3 promoted the metastasis of tumor cells by enhancing the glycolysis in them [ 39 ]. In our study, we divided the patients into high- and low-risk groups according to an established risk signature.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the pro-proliferation and anti-apoptotic functions of KLK8 may not be dependent on activation of Notch signaling pathway. Notably, our GSEA analysis data showed that KLK8 overexpression might also lead to the activation of EMT (epithelial-mesenchymal transition), glycolysis and KRAS signaling pathway, which have been implicated in the pathogenesis and progression of pancreatic cancers (17,(55)(56)(57). Whether these processes and the related signaling pathways contribute to the KLK8-induced pro-proliferation and antiapoptotic effects in pancreatic cancers merits further investigation.…”
Section: Discussionmentioning
confidence: 84%
“…These results suggest that the proproliferation and anti-apoptotic functions of KLK8 may not be dependent on activation of Notch signaling pathway. Notably, our GSEA analysis data showed that KLK8 overexpression might also lead to the activation of EMT (epithelial-mesenchymal transition), glycolysis and KRAS signaling pathway, which have been implicated in the pathogenesis and progression of pancreatic cancers [17,[43][44][45]. Whether these processes and the related signaling pathways contribute to the KLK8-induced pro-proliferation and anti-apoptotic effects in pancreatic cancers merits further investigation.…”
Section: Discussionmentioning
confidence: 84%
“…Staining intensity was scored as follows [16]: 0 = no color; 1 = yellow; 2 = light brown; and 3 = dark brown. The proportion of immune-positive tumor cells (number of positively labeled tumor cells / number of total tumor cells) was scored as follows [17]: 0, positive cells < 5%; 1, 6%-25% positive cells;2, 26%-50% positive cells; 3, positive cells 51%-75%; and 4 > 76%. ).…”
Section: Immunohistochemical (Ihc) Stainingmentioning
confidence: 99%